Maturation of Speech-Sound ERPs in 5–6-Year-Old Children: A Longitudinal Study - Linnavalli, Tanja; Putkinen, Vesa; Huotilainen, Minna; Tervaniemi, Mari (Frontiers in Neuroscience, 2018)
The maturation of 5–6-year-old children’s auditory discrimination – indicated by the development of the auditory event-related-potentials (ERPs) – is not previously studied in longitudinal settings. For the first time, we present here the results based on extensive dataset collected from 75 children. We followed the five- to six-year-olds for 20 months and measured their ERPs four times with the same multifeature paradigm with phonemic stimuli. The amplitude of the mismatch negativity (MMN) response increased during this time for vowel, vowel duration and frequency changes. Furthermore, the P3a component started to mature toward adult-like positivity for the vowel, intensity and frequency deviants and the late discriminative negativity (LDN) component decreased with age for vowel and intensity deviants. All the changes in the components seemed to happen during the second follow-up year, when Finnish children are taught letter symbols and other preliminary academic skills before going to school at the age of seven. Therefore, further studies are needed to clarify if these changes in the auditory discrimination are purely age-related or due to increasing linguistic knowledge of the children.